The cholera toxin B subunit induces trained immunity in dendritic cells and promotes CD8 T cell antitumor immunity - Tepale-Segura, Araceli; Gajón, Julián A.; Muñoz-Cruz, Samira; Castro-Escamilla, Octavio; Bonifaz, Laura C. (Frontiers in Immunology, 2024)
Introduction Innate immune training is a metabolic, functional, and epigenetic long-term reprogramming of innate cells triggered by different stimuli. This imprinting also reaches hematopoietic precursors in the bone marrow to sustain a memory-like phenotype. Dendritic cells (DCs) can exhibit memory-like responses, enhanced upon subsequent exposure to a pathogen; however, whether this imprinting is lineage and stimulus-restricted is still being determined. Nevertheless, the functional consequences of DCs training on the adaptive and protective immune response against non-infectious diseases remain unresolved. Methods We evaluated the effect of the nontoxic cholera B subunit (CTB), LPS and LTA in the induction of trained immunity in murine DCs revealed by TNFa and LDH expression, through confocal microscopy. Additionally, we obtained bone marrow DCs (BMDCs) from mice treated with CTB, LPS, and LTA and evaluated training features in DCs and their antigen-presenting cell capability using multiparametric cytometry. Finally, we design an experimental melanoma mouse model to demonstrate protection induced by CTB-trained DCs in vivo. Results CTB-trained DCs exhibit increased expression of TNFa, and metabolic reprogramming indicated by LDH expression. Moreover, CTB training has an imprint on DC precursors, increasing the number and antigen-presenting function in BMDCs. We found that training by CTB stimulates the recruitment of DC precursors and DCs infiltration at the skin and lymph nodes. Interestingly, training-induced by CTB promotes a highly co-stimulatory phenotype in tumor-infiltrating DCs (CD86+) and a heightened functionality of exhausted CD8 T cells (Ki67+, GZMB+), which were associated with a protective response against melanoma challenge in vivo. Conclusion Our work indicates that CTB can induce innate immune training on DCs, which turns into an efficient adaptive immune response in the melanoma model and might be a potential immunotherapeutic approach for tumor growth control.